Subfemtosecond Tracing of Molecular Dynamics during Strong-Field Interaction - Hanus, Vaclav; Kangaparambil, Sarayoo; Larimian, Seyedreza; Dorner-Kirchner, Martin; Xie, Xinhua; Schoeffler, Markus S.; Paulus, Gerhard G.; Baltuska, Andrius; Staudte, Andre; Kitzler-Zeiler, Markus (Physical Review Letters, 2019)
We introduce and experimentally demonstrate a method where the two intrinsic timescales of a molecule, the slow nuclear motion and the fast electronic motion, are simultaneously measured in a photoelectron photoion coincidence experiment. In our experiment, elliptically polarized, 750 nm, 4.5 fs laser pulses were focused to an intensity of 9×1014 W/cm2 onto H2. Using coincidence imaging, we directly observe the nuclear wave packet evolving on the 1sσg state of H2+ during its first round-trip with attosecond temporal and picometer spatial resolution. The demonstrated method should enable insight into the first few femtoseconds of the vibronic dynamics of ionization-induced unimolecular reactions of larger molecules.
CRIS-Team Scopus Importer:2023-04-20